PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - Putu Indah Devita Sari; Ni Nyoman Sri Rahayu Trisna Dewi; Ni Made Ernila Junipisa (Universitas Triatma Mulya, 2022)
This study aims to determine the effect of profitability ratios (ROA), liquidity ratios (CR), solvency ratios (DER) and activity ratios (TATO) on stock returns in banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The research sample is the financial statements of banking companies listed on the Indonesia Stock Exchange for the period 2018-2020. Sampling using purposive sampling technique. The data analysis technique used multiple linear regression analysis. Based on the results of the study it can be concluded that; 1) Profitability ratio proxied by Return On Assets (ROA) partially has a significant positive effect on Stock Return. 2) The liquidity ratio as proxied by the Current Ratio (CR) partially has a positive and insignificant effect on Stock Return. 3) Solvency Ratio proxied by Debt to Equity Ratio (DER) has a positive and insignificant effect on Stock Return. 4) Activity ratio proxied by Total Asset Turn Over (TATO) partially has a positive and insignificant effect on Stock Return